PANDANGAN MAHASISWA PENDIDIKAN MATEMATIKA: APAKAH SISWA AKAN MUDAH BELAJAR DENGAN PERMAINAN EDUKASI? - Nilza Humaira Salsabila; Nourma Pramestie Wulandari; Ulfa Lu’luilmaknun; Tabita Wahyu Triutami; Rhomiy Handican (Universitas Muhammadiyah Semarang, 2020)
The development of mobile games at this time can be utilized in the field of mathematics education. One of them by using educational games in mathematics learning. Teachers as instructors need to innovate in using learning media. The purpose of this study was to determine the views of students of mathematics education about the ease of students when learning to use math education games. This research is a quantitative descriptive study and the instrument used is a questionnaire about mathematics educational games. The study was conducted in the city of Mataram, West Nusa Tenggara with research subjects who are mathematics education students. There are 48 students; 11 males and 37 females. The results of the study showed that 45 students students agreed that mathematics education games made it easy for students to learn mathematics. As for some of the reasons raised, among others, educational games can increase students' understanding, interest, and enthusiasm for learning in mathematics.